Speech Functions In Dhar Mann’s Videos - Lisa Yudiarti (Universitas Muhammadiyah Sumatera Utara, 2021)
This research discusses Speech Functions in Dhar Mann’s Videos. The objectives of the research are to categorize the types of speech functions used in Dhar Mann’s videos, Analyze the realization of speech functions that are manifested in Dhar Mann’s videos, and explain the reason of speech functions in Dhar Mann’s videos. The research on this thesis was carried by using descriptive qualitative. The data were taken from script videos of Dhar Mann’s on the Instagram through IGTV feature. The data were analyzed and classified into four types of speech functions in the procedures namely statement, question, command, and offer. There are Statement (137 utterances, 72.49%), Question (34 utterances, 17.99%), Command (15 utterances, 7.93%) and Offer (3 utterances, 1.59%). The realization of Speech Function used Congruent and Metaphorical Coding. Speech Functions realized in Dhar Mann's Videos because this research will produce a deep understanding of the use of Speech Functions in the data used in this study. In addition, analyzing this video can provide information to listeners to better understand what the speaker is saying in the video. Keywords: speech function, realize and speech